Lim(x;4) (2x^2-7x-4)/(x^3-64) lim(x;-2) (3-sqrt(x+11))/x^2-4 lim(x;0) (1-cos6x)/x^2 

Lim(x;4) (2x^2-7x-4)/(x^3-64) lim(x;-2) (3-sqrt(x+11))/x^2-4 lim(x;0) (1-cos6x)/x^2 
Гость
Ответ(ы) на вопрос:
Гость
im(x;4) (2x^2-7x-4)/(x^3-64)=lim(x;4)(2(x-4)(x+0,5)/((x-4)(x^2+4x+16))=                                             =2(x+0,5)/(x^2+4x+16)=2(4+0,5)/(4^2+4*4+16)=                                             =2*4,5/48=9/48=3/16 lim(x;-2) (3-sqrt(x+11))/(x^2-4)= =lim(x;-2)(3-sqrt{x+11})(3+sqrt{x+11})/((x-2)(x+2)(3+sqrt{x+11}))= =lim(x;-2)(9-(x+11))/((x-2)(x+2)(3+sqrt{x+11}))= =lim(x;-2)(-2-x)/((x-2)(x+2)(3+sqrt{x+11}))= =lim(x;-2)(-(x+2))/((x-2)(x+2)(3+sqrt{x+11}))=lim(x;-2)(-1)/((x-2)(3+sqrt{x+11}))= =-1/((-2-2)(3+sqrt{-2+11}))=-1/(-4*(3+sqrt{9})=-1/(-4*(3+3))=1/24   lim(x;0) (1-cos6x)/x^2-не знаю
Не нашли ответ?
Ответить на вопрос
Похожие вопросы